Społeczna rola prawników: odpowiedzialność, podmiotowość, zaufanie - Kaczmarek, Przemysław (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
This article attempts to answer the question why is it worth to exhibit the category of agency in the legal practice. Answering the question I started my discussion from the presentation ideas related to the issue of the social role of the lawyers. In the completion of this objective, I discussed three ideas: moral responsibility, trust and subjective agency. Putting forward the role of the lawyer, I paid attention to the relationship between the notion of trust in the lawyer’s role and moral responsibility. This relationship is based on an ethical link, which is founded on a kind of obligation. This idea can be demonstrated by looking into confidence in the lawyer’s role as a special form of obligation to consider individual, institutional and social arguments. In the presented approach the state of limbo between the individual dimension, which focuses on the relationship between a specific individual and their rights, and the public dimension, where attention is paid to institutional and social arguments, is a characteristic feature of the professional role of a lawyer. The shaping of a professional role in a subjective and structural authorship is based on the idea of a two-way movement. It consists in highlighting the institutional structure with simultaneous reinforcement of the role of the subject who acts within it.